How might we best support the effective and meaningful employment of autistic people and improve outcomes?. Issue 1 (11th February 2021) - Cameron, Carl; Townend, Abbey
Abstract : Purpose: To determine the most appropriate and effective support to enable autistic people to gain and maintain employment in their chosen field. This paper aims to determine this and by which methods are most suitable for this kind of support, with a focus on mentoring. Design/methodology/approach: Mentoring is an intervention that has shown promise in assisting people who encounter barriers in finding work (for example, Roycroft, 2014). This research was conducted to determine whether the mentoring of autistic adults is effective in helping them to gain and maintain employment. The study examined the mentoring records of 90 autistic adults who were in receipt of funded mentoring with 18 separate organisations across England. Findings: The authors found that the nationally recognised statistic of autistic people in full-time employment as 16% (National Autistic Society, 2016) was ambitious and subject to regional variation. Based on the results of a programme providing employment and mentoring support that is available and accessible to autistic people, however, outcomes improve and employment is more likely to be achieved and maintained – including in areas of, especially low employment. It was found that 48% of autistic job seekers who were supported by specialist mentors found paid employment (full-time or part-time), demonstrating a 16% increase in paid employment between those who received mentoring support and those who did not. Research limitations/implications: A wider study across the UK would first determine if the nationally recognised figure is incorrect and also highlight those areas of the country which perform particularly well or badly. Originality/value: This paper believes that this is the only research of it is kind in the UK and that it is a springboard for others who have greater resources available to them. This study is two very early-career academics on the autism spectrum with limited resources available to us.